ANALISIS RISIKO POLITIK DAN EKONOMI DALAM EKSPANSI BISNIS INTERNASIONAL - VINCENSIA DEVI DWI CAHYANI; LUCY KRISTIAN, ERIVINA (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2025)
This study examines the influence of political and economic risks on the success of international business expansion within the context of increasing global integration. As companies venture into new markets, they encounter various challenges stemming from the complexity and diversity of the international business environment. Political risks—such as shifts in government policy, regional tensions, and political instability—are shown to significantly affect operational continuity and profitability. Likewise, economic risks, including exchange rate volatility, economic downturns, and fiscal policy changes, are critical in shaping long-term business sustainability abroad. Employing a case study approach and analyzing secondary data, this research identifies and evaluates the most salient risk factors companies must consider during strategic planning for expansion. The results indicate that firms achieving international growth are those adept at formulating and implementing robust, adaptive risk mitigation strategies, tailored to the unique political and economic landscapes of their target markets. This study offers valuable insights for business leaders and policymakers, highlighting the imperative of proactive and nuanced risk assessment to optimize opportunities and reduce potential losses in international ventures. The findings underscore the need for continuous monitoring and flexibility in strategic decision-making to navigate the ever-evolving global business arena effectively.